Journalists as Knowledge Brokers. (2nd January 2020) - Gesualdo, Nicole; Weber, Matthew S.; Yanovitzky, Itzhak
ABSTRACT: Knowledge brokers play a crucial role in improving the likelihood that scientific research informs public policy and professional practice, and journalists are well-positioned to serve in this role given their contributions to the flow and exchange of knowledge in society. To better understand the functions and mechanisms by which journalists may broker scientific knowledge, semi-structured interviews were conducted with a diverse sample of health and science journalists ( N = 22). Findings show that journalists actively seek to perform crucial knowledge brokering functions for their audiences, including searching for, filtering, corroborating, and incorporating research evidence into their reporting. At the same time, they stop short of consciously performing higher-order knowledge brokering functions, such as using research in their reporting to connect actors with a stake in the same issue or to advocate for the adoption of evidence-based policies and practices. Theoretical and practical implications of these findings are discussed.